Evaluation of the program for training standards for scientific research titles at Vietnam institute of science, technology and innovation - Hoang Thu Hien; Bui Hai Cuong; Dang Thu Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
The professional training program for public employees in the science and technology sector in Vietnam has been designed to enhance professional competencies, practical skills, and meet the title standards regulated by the State. This program plays a crucial role in improving the quality of human resources in science and technology, aligning with the country’s goals of innovation, international integration, and sustainable development. As of December 12, 2024, the program had been implemented across eight cohorts, with seven successfully completed and a total of 1,580 participants. After one year of implementation, a comprehensive evaluation of the program is necessary to assess its effectiveness, determine its sustainability, identify areas for improvement, and propose solutions to ensure the professional capacity of scientific research personnel. The study was conducted through a survey involving three key groups: 396 alumni, 35 representatives from managing agencies, and 10 experts. The survey results serve as a foundation for analyzing and evaluating the outcomes of the training program based on scientific title standards, thereby proposing solutions to enhance the quality, practicality, and effectiveness of future professional training efforts. Code: 25052003